Tetraspanin CD53 modulates lymphocyte trafficking but not systemic autoimmunity in Lyn‐deficient mice. Issue 10 (10th October 2021) - Yeung, Louisa; Gottschalk, Timothy A; Hall, Pam; Tsantikos, Evelyn; Gallagher, Rebecca H; Kitching, A Richard; Hibbs, Margaret L; Wright, Mark D; Hickey, Michael J
Abstract: The leukocyte‐restricted tetraspanin CD53 has been shown to promote lymphocyte homing to lymph nodes (LNs) and myeloid cell recruitment to acutely inflamed peripheral organs, and accelerate the onset of immune‐mediated disease. However, its contribution in the setting of chronic systemic autoimmunity has not been investigated. We made use of the Lyn −/− autoimmune model, generating Cd53 −/− Lyn −/− mice, and compared trafficking of immune cells into secondary lymphoid organs and systemic autoimmune disease development with mice lacking either gene alone. Consistent with previous observations, absence of CD53 led to reduced LN cellularity via reductions in both B and T cells, a phenotype also observed in Cd53 −/− Lyn −/− mice. In some settings, Cd53 −/− Lyn −/− lymphocytes showed greater loss of surface L‐selectin and CD69 upregulation above that imparted by Lyn deficiency alone, indicating that absence of these two proteins can mediate additive effects in the immune system. Conversely, prototypical effects of Lyn deficiency including splenomegaly, plasma cell expansion, elevated serum immunoglobulin M and anti‐nuclear antibodies were unaffected by CD53 deficiency. Furthermore, while Lyn −/− mice developed glomerular injury and showed elevated glomerular neutrophil retention above than that in wild‐type mice, absence of CD53 in Lyn −/− mice did not alter these responses. Together, these findings demonstrate that while tetraspanin CD53 promotes lymphocyte trafficking into LNs independent of Lyn, it does not make an important contribution to development of autoimmunity, plasma cell dysfunction or glomerular injury in the Lyn −/− model of systemic autoimmunity. Abstract : Tetraspanin CD53 controls immune cell trafficking in health and inflammatory disease, although its role in systemic autoimmunity remains unknown. Here we examined the role of CD53 in the Lyn‐deficient model of systemic autoimmune disease by generating CD53‐deficient Lyn −/− mice. The role of CD53 in controlling lymphocyte homing to lymph nodes persisted in the context of Lyn deficiency, although absence of CD53 did not alter development of systemic autoimmunity or renal inflammatory disease in Lyn −/− mice.